Establishment and characterization of a new human Ph+ erythroleukemic cell line, VES - Golemović, Mirna (Array, 2005)
Continuous human malignant hematopoietic cell lines are invaluable tool for hematological research. Here we report on a new erythroleukemic cell line termed VES that was established from the bone marrow mononuclear cells (BMNC) of a 22-year-old woman with Ph+ CML during her second post-transplant period. Actually, after unsuccessful allo-transplantation, the patient received auto-transplant that also failed to engraft. At the time of initiation of BMNC into culture for the analysis of stromal cell capacity, her bone marrow was tested Ph-negative by both FISH and PCR. Instead of establishment of an adherent stromal layer in vitro, blast-like cells appeared in the supernatant on day 27. These blast cells expressed highly amplified bcr/abl locus as shown by FISH, whereas the patient s bone marrow was still Ph-negative at the time. Following a very short period, the cultured cells started to express stable features of erythroleukemia cell line. Optimal growth was obtained by suspending the cells at concentration of 0.3x106 cells/ml in IMDM containing 10% FBS, 1% penicillin-streptomycin and 1% L-glutamine solution. After 3 days of culture, cell concentration varied between 1.3 and 1.8x106 cells/ml. VES cells were tested negative for the presence of EBV virus. For analysis of clonogenicity, VES cells at concentration of 103/ml were grown in a serum-free methylcellulose medium without cytokines (H4236 ; StemCell Tech., Canada). Following 7-day culture, 103 VES cells produced 251 42 and after 14 days 431 30 GF-independent colonies. Furthermore, on day 14 of the cell culture it was possible to observe reddish color of the colonies indicating the presence of hemoglobin. Cytological examination of cytospin preparations indicated homogenous population of leukemia blasts (>80%) the majority of them (>90%) being glycophorinA positive and MPO negative. Imunophenotyping and multiparameter flow cytometry revealed proerythroblastic lineage-associated profile: GlyA/CD235a+, CD11b+, CD15+, CD29+, CD33+, and CD117+. Conventional cytogenetics revealed complex karyotype with multiple numerical/structural abnormalities (MAKA), while metaphase FISH revealed the following aberrations: t(9 ; 22), 5q31, 7q31, +8, +6. Since FISH analysis detected highly amplified bcr/abl locus, we tested VES cells sensitivity to imatinib (Gleevec). Treatment with imatinib for 3 days (MTS assay) inhibited proliferation of VES cells with IC50 value of 0.2mM. Following 14 days of culture in methylcellulose medium with addition of 0.2mM imatinib, the clonogenic potential of VES cells was reduced by 55% in relation to untreated control. We demonstrated that imatinib induced apoptosis in VES cells in time- and dose-dependant manner, assessed with AnnexinV and PI staining, while there were no significant changes observed in the cell cycle except for a mild increase in cells in G0/G1 phase. Although further analyses are required, we believe that VES cells represent a new Ph+ erythroleukemia cell line and a suitable model for studying Ph+ malignant hematopoiesis in vitro